The Role Of Epitets In Expressing Poetical Intent In Saida Zunnunova's Poems - Xo‘jamberdiyeva Go‘zalxon Zafarjon qizi (Peerian Journals Publishing, 2026)
This article examines the repetitions used in the poems of Saida Zunnunova and their specific features. The epithet (adjective) category is one of the most important stylistic means of the language, which helps to create richer and more colorful images through words
Keywords: Epithet; compound epithet; phraseological epithet